Quality of life in patients with locally advanced breast cancer with disease progression after combination treatment - T. N. Popova; E. A. Kuzevanova (Опухоли женской репродуктивной системы)
Retrospective analysis of the long-term results of a study of quality of life in patients with locally advanced breast cancer wsurvival and disease progression after 3-5 years revealed that the quality of life in patients with recurrence substantially differed from that in those with good long-term results of treatment practically on all SF-36 scales.